Aid, Service Delivery, and the Millennium Development Goals in an Economy-wide Framework - Bourguignon, Francois; Diaz-Bonilla, Carolina; Lofgren, Hans (World Bank, Washington, DC, 2012)
In many developing countries, achieving the Millennium Development Goals (MDGs) by 2015 will require significant increases in expenditures on social services and in foreign assistance. It will also require careful planning of the sector allocation and sequencing of public spending. Especially for low-income countries, the challenges of the MDGs cannot be well understood unless sector issues are seen in the context of constraints at the macro level and in labor markets. To help countries analyze policies aimed at making progress toward the goals, the World Bank has developed a new tool, the Maquette for MDG Simulations (MAMS). Its originality is to fully integrate government services and their impact on the economy within an otherwise standard economy-wide dynamic framework. In comparison with existing approaches, MAMS offers three main advantages. First, the representation of the production of government services - such as health or education - takes into account demand as well as supply factors and the efficiency of these services. It also allows for interactions across the goals, and between the goals and economic growth. Second, it shows how scaling up these services has economy-wide impacts that may change resource allocation in the non-government sector and relative prices, including the unit cost of government services. Third, it shows the tradeoffs across time, including the relative costs and benefits, of front-loading expenditures versus back-loading. The present paper describes the basic features of MAMS and provides an illustration of its applicability for Ethiopia.